2010
DOI: 10.1186/1743-422x-7-119
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 Vpr: oligomerization is an essential feature for its incorporation into virus particles

Abstract: HIV-1 Vpr, a nonstructural viral protein associated with virus particles, has a positive role in the efficient transport of PIC into the nucleus of non-dividing target cells and enhances virus replication in primary T cells. Vpr is a 96 amino acid protein and the structure by NMR shows three helical domains. Vpr has been shown to exist as dimers and higher order oligomers. Considering the multifunctional nature of Vpr, the contribution of distinct helical domains to the dimer/oligomer structure of Vpr and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…For this purpose, we generated constructs containing TMPRSS2-ERG3 and TMPRSS2-ERG8 coding sequences fused to either N- or C-terminal coding sequences of the Venus reporter (Figure 4b). HIV-1 Vpr constructs were used as positive controls, as Vpr has been well characterized and shown to oligomerize [30]. As expected, we observed that VN-Vpr and VC-Vpr constructs co-transfected in HEK293 cells produced fluorescent signal, which was found to be localized in the nuclear region.…”
Section: Resultssupporting
confidence: 74%
“…For this purpose, we generated constructs containing TMPRSS2-ERG3 and TMPRSS2-ERG8 coding sequences fused to either N- or C-terminal coding sequences of the Venus reporter (Figure 4b). HIV-1 Vpr constructs were used as positive controls, as Vpr has been well characterized and shown to oligomerize [30]. As expected, we observed that VN-Vpr and VC-Vpr constructs co-transfected in HEK293 cells produced fluorescent signal, which was found to be localized in the nuclear region.…”
Section: Resultssupporting
confidence: 74%
“…Along those lines, previously published studies suggest that amino acid changes at niVpr positions 37 and 41 may affect Vpr oligomerization, which has been implicated in Vpr incorporation into nascent virions (Fritz et al , 2010; Venkatachari et al , 2010). Amino acids in this region of the protein (residues 36-46) have been shown to be critical for Vpr oligomerization (Zhao et al , 1994) and Vpr incorporation during virus assembly (Singh et al , 2000).…”
Section: Discussionmentioning
confidence: 86%
“…Based on the data, it was suggested that oligomerization of Vpr is essential for virion incorporation, and may also play a role in the events associated with virus infection (Venkatachari et al, 2010). In another study, BiFC was used to investigate intracellular interactions between APOBEC3G (A3G), RNA, and HIV-1 Gag.…”
Section: Virus-host Interactionsmentioning
confidence: 99%